Expression of insulin‐like growth factor‐1 receptor in circulating tumor cells of patients with breast cancer is associated with patient outcomes. Issue 1 (16th November 2017) - Spiliotaki, Maria; Mavroudis, Dimitris; Kokotsaki, Maria; Vetsika, Eleni‐Kyriaki; Stoupis, Ioannis; Matikas, Alexios; Kallergi, Galatea; Georgoulias, Vassilis; Agelaki, Sofia
Abstract : In patients with breast cancer, markers of aggressiveness such as dysregulation of the insulin‐like growth factor receptor (IGF1R) system and E‐cadherin loss are commonly observed. Reduced IGF1R expression is correlated with decreased E‐cadherin levels and increased cell motility. We assessed IGF1R and E‐cadherin expression in circulating tumor cells (CTCs) in patients with breast cancer. Peripheral blood mononuclear cells of early ( n  = 87)‐ and metastatic ( n  = 126)‐stage breast cancer patients (obtained prior to adjuvant and first‐line chemotherapy) were evaluated using double immunofluorescence (IF) staining for cytokeratin (CK) and IGF1R. Triple IF using CK, IGF1R, and E‐cadherin antibodies was performed in selected CTC(+) patients. IGF1R(+) CTCs were more frequently observed in early disease than in metastatic disease (86% vs 68% of CTCs, P  = 0.04) stage, whereas IGF1R(−) CTCs were more common in metastatic than in early disease (32% vs 14% of CTCs, P  = 0.002). 100% of CTC(+) patients with early disease, compared to 79% of those with metastatic disease, harbored IGF1R(+) CTCs ( P  = 0.007). Patients with early disease and exclusively IGF1R(+) CTCs had longer disease‐free ( P  = 0.02) and overall survival ( P  = 0.001) compared to patients with both IGF1R(+) and IGF1R(−) CTC populations. 67% of early‐stage CTC(+) patients evaluated had exclusively IGF1R(+)/E‐cadherin(+) CTCs, 33% also had IGF1R(−)/E‐cadherin(−) CTCs, and none had exclusively IGF1R(−)/E‐cadherin(−) CTCs compared to 17%, 75%, and 8% of metastatic patients, respectively ( P  = 0.027). Similarly, in paired samples of patients with early disease that progressed to metastatic disease, the proportion of IGF1R(+)/E‐cadherin(+) CTCs was reduced and IGF1R(−)/E‐cadherin(−) CTCs were increased in the metastatic stage compared to early disease stage. IGF1R(+) CTCs are commonly detected in breast cancer, and their frequency decreases in the metastatic disease stage. IGF1R(+)/E‐cadherin(+) CTCs also decrease in metastatic patients. IGF1R(+) CTCs are associated with favorable outcomes in early disease stage, suggesting that IGF1R expression is correlated with reduced metastatic potential in breast cancer. Abstract : Insulin‐like growth factor‐1 receptor (IGF1R) is commonly expressed in the circulating tumor cells (CTCs) of early‐ and metastatic‐stage breast cancer. IGF1R and E‐cadherin are coexpressed at the single CTC level, and their expression rate decreases in metastatic‐stage cancer compared to early‐stage disease. IGF1R‐expressing CTCs are associated with favorable outcomes in early‐stage breast cancer.